Simultaneous Use of Kocher-Langenbeck and Lateral Window Approaches for Transverse Acetabular Fracture Open Reduction and Internal Fixation: A Case Report. Issue 4 (October 2019) - Moran, Thomas; Hadeed, Michael M.; Yildirim, Baris; Mathur, Kishan; Yarboro, Seth R.
Abstract : Case: An otherwise healthy 39-year-old man presented after a fall from 30 feet with a right transverse, transtectal acetabular fracture. The fracture was not reducible with an isolated anterior or posterior approach. A simultaneous combined approach was used in the lateral decubitus position. The fracture was appropriately reduced and stabilized. Conclusions: This combined approach with the patient in the lateral decubitus position was effective without requiring repositioning of the patient during surgery. This technique may be helpful for reduction of challenging transverse acetabular fractures.